Transversalización del eje medio ambiente en educación superior: el caso de la UACYTI-UAGro (2019)
Mainstreaming is a viable strategy for strengthening environmental content in the curriculum and promoting social responsibility. In this sense, the article is oriented to design a methodological procedure to transversalize the environmental axis in the study plan of the career in Sciences and Information Technologies of the Autonomous University of Guerrero (Mexico). The methodology addresses four phases: diagnosis of teachers' perception of environmental knowledge; design of a training pro-posal; construction of environmental competence; and development of the methodological proposal. Among the results, the low integration of environmental competence into the learning unit stands out; most teachers do not suggest the integration of competencies, but show interest in contributing to the formation of environmentally responsible graduates. It is concluded that the environmental axis should be integrated into the educational programs; teachers should be trained to contribute to the training of professionals with the required competencies and to act with social and environmental responsibility.